Clinical Efficacy and Safety of Trans-Sacral Epiduroscopic Laser Decompression Compared to Percutaneous Epidural Neuroplasty - Bong Ju Moon; Seong Yi; Yoon Ha; Keung Nyun Kim; Do Heum Yoon; Dong Ah Shin (Pain Research and Management)
Percutaneous epidural neuroplasty (PEN) is an effective and safe procedure for herniated lumbar disc (HLD). Although PEN has an advantage of adhesiolysis, this procedure cannot decompress the protruded disc. Recently, trans-sacral epiduroscopic laser decompression (SELD) for HLD has been introduced as a promising alternative methodology. This study evaluated the clinical efficacy and safety of SELD compared to PEN, as well as the change in protruded disc volume after SELD through pre- and postoperative magnetic resonance imaging (MRI), in patients with HLD. Thirty consecutive patients underwent SELD (SELD group), and 45 patients underwent PEN (PEN group). The Visual Analog Scale (VAS) for leg pain; Oswestry Disability Index (ODI); 12-Item Short-Form Health Survey (SF-12); preoperative and postoperative 4-, 12-, and 24-week Macnab criteria; and preoperative and 24-week postoperative lumbar spinal MRIs after SELD were obtained. There was no significant difference in age, sex, duration of symptoms, and the distributions of disc level between the two groups (all P>0.05). Between the SELD and PEN groups, preoperative VAS, ODI, and SF-12 scores had no significant differences. However, the VAS, ODI, and SF-12 scores improved significantly after the procedures by postoperative week 24 in each group (all P<0.05). Furthermore, improvements of VAS, ODI, SF-12, and success rate of Macnab criteria in the SELD group were better than those in the PEN group (all P<0.05). The protruded disc volume after SELD decreased significantly (P=0.034). All clinical and functional outcomes of patients undergoing SELD and PEN for HLD improved following the procedures. Notably, SELD was superior to PEN regarding the degree of improvement in clinical and functional outcomes. Therefore, we suggest that SELD can be used as an effective alternative to PEN to provide improved clinical and functional outcomes in patients with HLD.